Association between depression and macrovascular disease: a mini review - Zhao, Shuwu; Zhu, Liping; Yang, Jinfeng (Frontiers in Psychiatry, 2023)
Depression and macrovascular diseases are globally recognized as significant disorders that pose a substantial socioeconomic burden because of their associated disability and mortality. In addition, comorbidities between depression and macrovascular diseases have been widely reported in clinical settings. Patients afflicted with coronary artery disease, cerebrovascular disease or peripheral artery disease exhibit an elevated propensity for depressive symptoms. These symptoms, in turn, augment the risk of macrovascular diseases, thereby reflecting a bidirectional relationship. This review examines the physiological and pathological mechanisms behind comorbidity while also examining the intricate connection between depression and macrovascular diseases. The present mechanisms are significantly impacted by atypical activity in the hypothalamic-pituitary-adrenal axis. Elevated levels of cortisol and other hormones may disrupt normal endothelial cell function, resulting in vascular narrowing. At the same time, proinflammatory cytokines like interleukin-1and C-reactive protein have been shown to disrupt the normal function of neurons and microglia by affecting blood-brain barrier permeability in the brain, exacerbating depressive symptoms. In addition, platelet hyperactivation or aggregation, endothelial dysfunction, and autonomic nervous system dysfunction are important comorbidity mechanisms. Collectively, these mechanisms provide a plausible physiological basis for the interplay between these two diseases. Interdisciplinary collaboration is crucial for future research aiming to reveal the 2 pathogenesis of comorbidity and develop customised prevention and treatment strategies.